PENGARUH EMPATI EMOSIONAL TERHADAP PERILAKU PROSOSIAL YANG DIMODERASI OLEH JENIS KELAMIN PADA MAHASISWA - Muammar Arfah Rasyid; Muhammad Al Fayed; Muhammad Yasin Ansari B; Muhammad Rahmat; Muhammad Nur Fath M; Adelia Kurnia Sari B; Syahrul Jamal (Jurnal Psikologi TALENTA, 2020)
The research aims to determine the effect of emotional on prosocial behavior moderated by gender in new students of psychology UNM. Emotional empathy is defined as an impulse automatically and without being realized to respond to other people's emotional states. And prosocial behavior is defined as an act by giving two treatments in the form of a video which can increase someone’s empathy or neutral with an instrument to measure emotional empathy using the Positive and Negative Affect Scale (PANAS) developed by Watson, Clark & Tellegen (1988). The measurement of prosocial behavior is done by looking at the number of donations given by respondents. The research respondents numbered 32 students consisting of men and women with the criteria of new students in UNM psychology. This experimental research used factorial design 2 (empathy: neutral vs empathy) X 2 (sex: male vs. female) between-subject designs. The results of this study indicate that there is a significant influence between emotional empathy on prosocial behavior, but the effect of gender as a moderator on prosocial behavior does not have a significant effect.